DETERMINAN KEPUTUSAN PEMBAYARAN ZAKAT MENGGUNAKAN E-COMMERCE DI KOTA MALANG - Zahirah, Ishmah; Sri Muljaningsih (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
The economic imbalance in Indonesia, if not given attention, has the potential to increase, worsening economic growth conditions. Zakat Infaq Shadaqah (ZIS), as an instrument of wealth redistribution in the sharia economy, has the potential to overcome this problem, but currently there is a gap between the potential and realization of ZIS, especially regarding the collection of funds which is not yet optimal. To overcome this problem, this research aims to analyze the factors that influence the decision to pay ZIS via Shopee and Tokopedia, the two largest e-Commerce platforms that provide digital ZIS payment services. The factors analyzed include digital financial literacy, promotion, demographics, and preferences in e-Commerce. This research uses quantitative methods with multinomial logistic regression using SPSS 24. The research population is residents of Malang City, with a sample of 100, taken using a purposive sampling method. The results of the analysis show that the factors age, digital financial literacy, promotion, e-commerce, ZIS preferences are proven to have a significant influence on the Platform Decision to fulfill ZIS in e-Commerce. Furthermore, this research finds that there is an insignificant influence of education level and gender.